New species of Tychini from Turkey and Japan (Coleoptera: Staphylinidae: Pselaphinae) - Sabella, Giorgio; Besuchet, Claude; Kurbatov, Sergey A. (Zootaxa, 2011)
Seven new species of Tychini are described: Tychus viti Besuchet sp. n. (dalmatinus group), T. sodalicius Kurbatov sp. n. (cilicicus group), T. latebrosus Besuchet sp. n. (judaeus group), T. spurius Sabella sp. n. (mutabilis group), T. grassator Sabella sp. n. (florentinus group), and T. altivagus Besuchet sp. n. (incertae sedis), all from Turkey, and Tainochus bastardus Kurbatov sp. n. from Japan, Yamanashi Pref. Tychus anser Sabella & Kurbatov, 2002 is assigned to Tychus mutabilis species group while Tychus coiffaiti Besuchet, 1958 is included in Tychus florentinus species group. New localities for Tychus meleagris Sabella & Kurbatov, 2002, T. anser Sabella & Kurbatov, 2002, Tainochus minutus Nomura, 1996, T. iwaoi Nomura, 1996, and T. insulicola Nomura & Lee, 1992 are reported.